When will Energy Sector be serious about appalling condition? - Thanju, Jeewan P. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
DOI: http://dx.doi.org/10.3126/hn.v8i0.4899 Hydro Nepal Issue No. 8, 2011 January Page: 5-6 Uploaded date: 16 June, 2011